2017
DOI: 10.1111/jnc.14153
|View full text |Cite
|
Sign up to set email alerts
|

The role of exercise in mitigating subcortical ischemic vascular cognitive impairment

Abstract: Subcortical ischemic vascular cognitive impairment (SIVCI) is the most preventable form of cognitive dysfunction. There is converging evidence from animal and human studies that indicate vascular injury as the primary cause of SIVCI. Currently, there are no curative pharmaceutical treatments for vascular dementia; however, exercise may be a promising strategy to combat SIVCI. This review will focus on the role of exercise as a strategy to prevent or slow the progression of SIVCI, with particular emphasis on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 142 publications
(303 reference statements)
0
13
0
Order By: Relevance
“…In support of these findings, a recent review had concluded that exercise increases the bioavailability of neurotrophins, protects blood vessels from damage, and reduces vascular disease risk factors in patients with subcortical ischemia. Apart from these, it was noted that exercise improves the cognitive function in this subset of patients (Dao et al, 2018).…”
Section: Therapeutic Approaches In Csvdmentioning
confidence: 97%
“…In support of these findings, a recent review had concluded that exercise increases the bioavailability of neurotrophins, protects blood vessels from damage, and reduces vascular disease risk factors in patients with subcortical ischemia. Apart from these, it was noted that exercise improves the cognitive function in this subset of patients (Dao et al, 2018).…”
Section: Therapeutic Approaches In Csvdmentioning
confidence: 97%
“…Exercise is an established safe and effective therapy for managing numerous adverse effects of cancer treatment, including fatigue, psychological distress, functional decline, and detrimental body composition changes [ 73 ]. Accumulating evidence on the positive role of exercise on improving cognitive function in healthy older adults and those with mild cognitive impairment or more severe neurocognitive impairment (i.e., AD, stroke) has sparked significant interest in the potential use of exercise as an effective management strategy for CRCI [ 74 , 75 , 76 ]. A variety of evidence supports the conclusion that exercise link to cancer which could lower the risk of different cancers including colon, breast, kidney, endometrial, bladder, esophageal, and stomach cancers, with moderate evidence for lung cancer.…”
Section: Role Of Exercise In Crcimentioning
confidence: 99%
“…As there is currently no cure for WMHs (Alber et al, 2019), strategies which can mitigate the risks of WMH on falls are needed. Physical activity (PA) is an important modifiable lifestyle factor associated with both lower WMH volumes (Burzynska et al, 2014;Dao et al, 2018;Alber et al, 2019) and reduced risk of falling (Khan et al, 2001). However, whether PA moderates the burden of WMH volume on falls risk is not well established.…”
Section: Introductionmentioning
confidence: 99%
“…Lifestyle factors, such as PA, are a possible avenue to prevent and/or reverse WMH progression (Torres et al, 2015;Dao et al, 2018). PA is defined as any bodily movement produced by skeletal muscles that requires energy expenditure (Caspersen et al, 1985).…”
Section: Introductionmentioning
confidence: 99%